Proteomic Analysis Reveals Salicylic Acid as a Pivotal Signal Molecule in Rice Response to Blast Disease Infection - Haiying Zhou; Delight Hwarari; Yunhui Zhang; Xiaosong Mo; Yuming Luo; Hongyu Ma (Plants, 2022)
Rice blast disease caused by a fungus, Magnaporthe grisea, is one of the most destructive diseases in rice production worldwide, and salicylic acid (SA) can efficiently decrease the damage of M. grisea. Here, we combined the 2-Dimensional-Liquid Chromatography and the Matrix-assisted laser desorption/ionization time-of-flight mass spectrometer (2D-LC-MALDI-TOF-TOF MS) techniques to compare and identify differentially expressed labelled proteins by the isobaric tags for relative and absolute quantitation (iTRAQ) between the blast-resistant cultivar Minghui and the susceptible rice cultivar Nipponbare in response to blast fungus infection. The group samples were treated with salicylic acid and compared to control samples. A total of 139 DEPs from the two cultivars showed either more than a two-fold change or alternating regulation patterns. Protein functionality analysis also exhibited that these proteins are involved in a wide range of molecular functions including: energy-related activity (30%), signal transduction (11%), redox homeostasis (15%), amino acid and nitrogen metabolism (4%), carbohydrate metabolism (5%), protein folding and assembly (10%), protein hydrolysis (9%), protein synthesis (12%), and other unknown functions (4%). Specifically, we demonstrated that exogenous treatment with salicylic acid promoted recovery in both rice cultivars from Magnaporthe grisea infection by enhancing: the regulation of signal transduction, increasing energy conversion and production through the regulation of the glycolytic pathway, and other various biochemical processes. These findings may facilitate future studies of the molecular mechanisms of rice blast resistance.